Regret and Therapeutic Decisions in Multiple Sclerosis Care: Literature Review and Research Protocol - Saposnik, Gustavo; Bueno-Gil, Guillermo; Sempere, Ángel P.; Rodríguez-Antigüedad, Alfredo; del Río, Beatriz; Baz, Mar; Terzaghi, María; Ballesteros, Javier; Maurino, Jorge (Frontiers in Neurology, 2021)
Background: Decisions based on erroneous assessments may result in unrealistic patient and family expectations, suboptimal advice, incorrect treatment, or costly medical errors. Regret is a common emotion in daily life that involves counterfactual thinking when considering alternative choices. Limited information is available on care-related regret affecting healthcare professionals managing patients with multiple sclerosis (MS). Methods: We reviewed identified gaps in the literature by searching for the combination of the following keywords in Pubmed: “regret and decision,” “regret and physicians,” and “regret and nurses.” An expert panel of neurologists, a nurse, a psychiatrist, a pharmacist, and a psychometrics specialist participated in the study design. Care-related regret will be assessed by a behavioral battery including the standardized questionnaire Regret Intensity Scale (RIS-10) and 15 new specific items. Six items will evaluate regret in the most common social domains affecting individuals (financial, driving, sports—recreation, work, own health, and confidence in people). Another nine items will explore past and recent regret experiences in common situations experienced by healthcare professionals caring for patients with MS. We will also assess concomitant behavioral characteristics of healthcare professionals that could be associated with regret: coping strategies, life satisfaction, mood, positive social behaviors, occupational burnout, and tolerance to uncertainty. Planned Outcomes: This is the first comprehensive and standardized protocol to assess care-related regret and associated behavioral factors among healthcare professionals managing MS. These results will allow to understand and ameliorate regret in healthcare professionals. Spanish National Register (SL42129-20/598-E).